2015
DOI: 10.5539/gjhs.v7n4p173
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Persian Version of the 8-Item Morisky Medication Adherence Scale (MMAS-8) in Iranian Hypertensive Patients

Abstract: The reliability and validity of the 8-item Morisky Medication Adherence Scale (MMAS-8) was assessed in a sample of Iranian hypertensive patients. In this multi-center study which lasted from August to October 2014, a total of 200 patients who were suffering from hypertension (HTN) and were taking anti-hypertensive medication(s) were included. The cases were accessed through private and university health centers in the cities of Tehran, Karaj, Kermanshah, and Bafgh in Iran and were interviewed face-to-face by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 20 publications
5
58
1
4
Order By: Relevance
“…In the treatment of hypertension, poor adherence affects the clinical outcome; hence 32.8% of DTPs were nonadherence with the prescribed medications. The significant association between adherence level and BP control was also supported by other studies 21 .Therefore, close monitoring of patients with hypertension is vital in order to trace any possible factor that could contribute to the poor control of BP while taking appropriate management. By doing so, it could be possible to prevent CV complications as well as minimize the occurrence of DTPs that might be resulted due to poor BP control.…”
Section: Discussionsupporting
confidence: 59%
“…In the treatment of hypertension, poor adherence affects the clinical outcome; hence 32.8% of DTPs were nonadherence with the prescribed medications. The significant association between adherence level and BP control was also supported by other studies 21 .Therefore, close monitoring of patients with hypertension is vital in order to trace any possible factor that could contribute to the poor control of BP while taking appropriate management. By doing so, it could be possible to prevent CV complications as well as minimize the occurrence of DTPs that might be resulted due to poor BP control.…”
Section: Discussionsupporting
confidence: 59%
“…The present study revealed that more than half of the hypertensive patients who participated in our study had poor adherence to their medications based on P-MMAS-8. In a systematic review, Nielson et al revealed remarkable (15). Given that adherence to medication and other non-pharmacological recommendations is necessary to control the disease and prevent its complications, measuring adherence to treatment by a simple, valid, and reliable instrument should be included in follow-up visits in primary health care (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Acceptable reliability and validity were reported for the original and other versions (including Persian one) (12)(13)(14). Moharamzad et al revealed that the Persian version of the MMAS-8 had acceptable validity and reliability (Cronbach's Alpha coefficient: 0.69 and ICC = 0.940) in Iranian hypertensive patients (15).…”
Section: Methodsmentioning
confidence: 99%
“…The total MMAS score ranges from 0 to 8 and the adherence level could be categorized as high (score = 8), moderate (score = 6 to < 8), and low (score < 6) (14). Moreover, the original researchers suggested a cutoff point of six to categorize the MMAS scores and this method was applied by other researchers, as well (8,15,16). For data analysis, the patients were classified into two groups: non-adherent (MMAS score < 6) and adherent patients (MMAS score ≥ 6).…”
Section: Methodsmentioning
confidence: 99%